NUMERICAL MODELLING OF A MANTLE PLUME: THE PLUME HEAD-LITHOSPHERE INTERACTION IN THE FORMATION OF AN OCEANIC LARGE IGNEOUS PROVINCE - d'Acremont E.; Leroy S.; Burov E.B. (My University, 2003)
The thermomechanical processes associated with formation of large igneous provinces (LIPs) remain poorly understood owing to fundamental difficulties in simulating plume–lithosphere interactions in current numerical models. These models, which aim to simulate the rise of mantle plume and the spread of plume head material, imply a mechanically over-simplified lithosphere and, commonly, a flat lithosphere (zero vertical displacement) as the upper boundary condition. We propose a new numerical model, derived from lithospheric-scale models. It has a high numerical resolution in the lithospheric domain and explicitly accounts for: (1) free upper surface boundary condition, (2) elastic–plastic–ductile lithospheric rheology, including surface faulting, and (3) vertical strength variations in the lithosphere. We study the final stages of plume ascent and we focus on surface and lithospheric evolution and intra-plate strain localisations. The experiments predict that the first surface elevation occurs in less than 0.2 Ma after plume initiation at 400 km depth. Variation of rheological parameters results in different surface elevations (500–2500 m), ascent (2–10 m/yr) and base plate strain rates (10−12–10−15 s−1). Fast (0.2–0.3 m/yr) plume head flattening starts at the moment when the plume head reaches the base of the lithosphere. It leads to large-scale extension and deep normal faulting at the centre of the plateau, and to strong thermomechanical erosion at its base. The erosion is maximal not under the plume centre (as was predicted before), but in two large bordering zones. Our study locally is the igneous province of the Caribbean plate where the pre-existing (Farallon) lithosphere has been affected by the Galapagos hotspot activity that generated thermal perturbations and crustal thickening with two main episodes of volcanism and underplating.
Keywords: oceanic large igneous province; mantle plume; numerical model; lithospheric scale